Implementation of Teacher Performance Management in Improving Learning Quality at SD Muhammadiyah Sukorejo: Implementasi Manajemen Kinerja Guru dalam Meningkatkan Mutu Pembelajaran di SD Muhammadiyah Sukorejo - Fatikhin, Agus Sukron Muh (Prosiding University Research Colloquium, 2024)
This study examines teacher performance manajement in an effort to improve the quality of learning which focuses on planning, organizing, implementing, and evaluating teacher performance manajement at SD Muhammadiyah Sukorejo. The research was conducted in December 2022. The method used in this research is a qualitative descriptive method. The key informants in this study were the principals of SD Muhammadiyah Sukorejo with the support of informants from SD Muhammadiyah Sukorejo teachers. Data collection uses several guidelines including guidelines for interviews, observation, and documentation studies. The teacher performance improvement program at SD Muhammadiyah Sukorejo has been effectively implemented by the school. This can be seen when the school held a performance planning meeting which was held a few days before the end of the school year. However, based on the implementation of teacher performance improvement manajement, several problems were found, namely external problems and internal problems.